Acetyl-L-Carnitine Supplementation During HCV Therapy With Pegylated Interferon-α 2b Plus Ribavirin: Effect on Work Performance; A Randomized Clinical Trial - Malaguarnera, Giulia (Kowsar, 2014)
BACKGROUND: The health status of employees with chronic hepatitis C has major implications for organizations and labour market. OBJECTIVES: To assess the effects of Acetyl-L-Carnitine administration on work productivity, daily activity, and fatigue in subjects with chronic hepatitis C treated with Pegylated-Interferon-α2b and Ribavirin. PATIENTS AND METHODS: In this prospective, randomized, placebo controlled, double blind clinical trial, 30 subjects (Group A) with chronic hepatitis, received Pegylated-Interferon-α2b (1.5 mg/kg per week) plus Ribavirin and placebo, while 32 subjects (Group B) received the same dosage of Pegylated-Interferon-α2b plus Ribavirin plus 2g Acetyl-L-Carnitine twice per day, for 12 months. Work productivity loss, impairment in daily activities, presenteeism, absenteeism, have been assessed using the Work Productivity and Activity Impairment questionnaire. We also evaluated severity of fatigue, mental fatigue and physical fatigue. RESULTS: Significant difference were observed in physical fatigue, mental fatigue and severity of fatigue, aspartate aminotransferase, alanine aminotransferase, and viremia after 12 months treatment. In Group B we observed a significant decrease of presenteeism and daily activity impairment after 6 months, 12 months and at follow up. A significant increase of work productivity was observed after 12 months and at follow up. CONCLUSIONS: Office workers with chronic hepatitis C, treated with Pegylated-Interferon-α2b plus Ribavirin, had work performance loss. In subjects treated with Acetyl-L-Carnitine supplementation we observed increased daily activity and reduced presenteeism and fatigue. Acetyl-L-Carnitinegroup had a smaller reduction of productivity comparing to placebo group.